(untitled) (Research, Society and Development, 2024)
Introduction: The term “mechanical ventilation” (MV) refers to a series of techniques that replace the ventilatory function of the lungs, with the main objective of providing support in the treatment of patients suffering from acute or chronic respiratory failure, totally or partially replacing spontaneous ventilation. , configuring one of the ways of approaching the patient with ARDS, however, when governed in the conventional way, it can affect the lung, enhancing an inflammatory process in it, and as prevention, the protective strategy is used. Objective: to describe the main current scientific evidence on protective MV in patients with ARDS. Methodology: This is an integrative review of the literature. The search for primary studies took place in the databases: PubMed and Scielo. Results: 35 articles were found within the search strategy established using the descriptors Respiratory Distress Syndrome, Lung Injury, and Protection. Of these, 5 fit with the research theme. Conclusion: ∆P is the main predictor of mortality in ARDS.